IMPLEMENTASI KRIPTOGRAFI DENGAN METODE ELLIPTIC CURVE CRYPTOGRAPHY (ECC) UNTUK APLIKASI CHATTING DALAM CLOUD COMPUTING BERBASIS ANDROID - ainur rilo taqwa; Danang Haryo Sulaksono (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2020)
in general, information dissemination facilities in the current technological era can be done quicklyand easily through the android application media. One of the most frequently used media forinformation dissemination is chatting. The problem with this research is that the chat application allowssomeone to send messages or files to other users who have access rights, with the risk that the data willbe seen by anyone who has access rights in it. This can happen because in the chat application can seeanything that is shared as long as you have access rights, but sometimes there is some data that isprivacy. So it is necessary to add a means to secure this privacy data so it cannot be seen by other users.The solution to overcome this problem is a cryptographic system. One cryptographic method thatprovides solutions to information security problems is the Elliptic Curve Cryptography (ECC) method.Therefore this thesis proposal is to create an online system in order to implement cryptography with theElliptic Curve Cryptography (ECC) method for Android-based chat applications. The testing processin this study using 25 image data obtained, the smallest avalanche effect value is 36.52801638, thebiggest avalanche effect is 94,67749211. And obtained an average avalanche effect value of79,8881925. The average avalanche effect that produces a large enough percentage proves that theapplication is running well, because the greater the percentage obtained, the better the application isrunning. From the above test it can be concluded that the Elliptic Curve Cryptography (ECC) algorithmmethod is effective for hiding data files in chat applications that are privacy ABSTRACTIn general, information dissemination facilities in the current technological era can be done quicklyand easily through the android application media. One of the most frequently used media forinformation dissemination is chatting. The problem with this research is that the chat application allowssomeone to send messages or files to other users who have access rights, with the risk that the data willbe seen by anyone who has access rights in it. This can happen because in the chat application can seeanything that is shared as long as you have access rights, but sometimes there is some data that isprivacy. So it is necessary to add a means to secure this privacy data so it cannot be seen by other users.The solution to overcome this problem is a cryptographic system. One cryptographic method thatprovides solutions to information security problems is the Elliptic Curve Cryptography (ECC) method.Therefore this thesis proposal is to create an online system in order to implement cryptography with theElliptic Curve Cryptography (ECC) method for Android-based chat applications. The testing processin this study using 25 image data obtained, the smallest avalanche effect value is 36.52801638, thebiggest avalanche effect is 94,67749211. And obtained an average avalanche effect value of79,8881925. The average avalanche effect that produces a large enough percentage proves that theapplication is running well, because the greater the percentage obtained, the better the application isrunning. From the above test it can be concluded that the Elliptic Curve Cryptography (ECC) algorithmmethod is effective for hiding data files in chat applications that are privacy.Keywords: Cryptography, Elliptic Curve Cryptography (ECC) Algorithm, Avalanche EffectABSTRAKSecara umum, fasilitas penyebaran informasi pada era teknologi yang saat ini dapat dilakukan dengancepat dan mudah melalui media aplikasi android. Salah satu media yang paling sering digunakan untukpenyebaran informasi adalah chatting. Masalah dari penelitian ini adalah aplikasi chattingmemungkinkan seseorang dapat mengirim pesan ataupun file kepada user lain yang telah memiliki hakakses, dengan resiko datanya akan dapat dilihat oleh siapa saja yang memiliki hak akses didalamnya.Hal ini dapat terjadi karena didalam aplikasi chatting tersebut dapat melihat apapun yang dibagi selamamemiliki hak akses, namun terkadang ada beberapa data yang bersifat privasi. Sehingga perluditambahkan suatu sarana untuk mengamankan data privasi ini agar tidak dapat dilihat oleh user lain.Adapun solusi untuk mengatasi hal tersebut maka dibuatlah sebuah sistem kriptografi. Salah satumetode kriptografi yang memberikan solusi untuk permasalahan keamanan informasi adalah metodeElliptic Curve Cryptography (ECC). Oleh karena itu proposal skripsi ini untuk membuat sebuah sistemonline agar dapat mengimplementasikan cryptography dengan metode Elliptic Curve Cryptography(ECC) untuk aplikasi chatting berbasis Android. Proses pengujian pada penelitian ini menggunakan 25data citra didapatkan, nilai avalanche effect terkecil adalah 36,52801638, avalanche effect terbesaradalah 94,67749211. Dan didapatkan nilai avalanche effect rata – rata sebesar 79,8881925. Nilai rata –rata avalanche effect yang menghasilkan persentase yang cukup besar membuktikan bahwa aplikasiberjalan dengan baik, karena semakin besar persentase yang didapatkan maka semakin baik aplikasi ituberjalan. Dari pengujian diatas dapat disimpulkan bahwa metode algoritma Elliptic Curve Cryptography(ECC) ini efektif untuk menyembunyikan file data pada aplikasi chatting yang bersifat privasi.Kata Kunci : Kriptografi, Algoritma Elliptic Curve Cryptography (ECC), Avalanche Effect